High levels of androgens cause chondrocyte accumulation and loss of smooth muscle in the mouse penile body. Issue 6 (18th February 2020) - Hiremath, Deepak S; Geerling, Elizabeth C; Hai, Lan; Narayan, Prema
Abstract: Androgens are essential for penile development and for maintaining penile structural and functional integrity. Loss of androgen levels or function results in a decrease in smooth muscle content, accumulation of adipocytes in the corpora cavernosa, and inhibition of erectile function. Our previous studies with a mouse model (KiLHR D582G ) of constitutive luteinizing hormone receptor activity also showed structural abnormalities in the penis caused by a decrease in smooth muscle content, accumulation of chondrocytes, and sexual dysfunction. As KiLHR D582G mice exhibit very high levels of testosterone at all postnatal ages, the goal of this study was to determine if the elevated androgen levels were responsible for the morphological changes in the penis. Implantation of testosterone capsules in wild-type mice at neonatal (2 weeks) and postpubertal (5 weeks) ages resulted in the accumulation of chondrocytes in the corpora cavernosa of the adult animals. Mice implanted with testosterone capsules at 2 weeks of age exhibited a 4-fold increase in serum testosterone with a 1.5-fold loss of smooth muscle at 24 weeks of age. Collagen content was unchanged. Only 57% of testosterone implanted mice were fertile at 24 weeks of age. Mice implanted with testosterone capsules at 5 weeks of age showed no decrease in smooth muscle content at 24 weeks, although serum testosterone levels were elevated 5-fold. Implantation with dihydrotestosterone also resulted in chondrocyte accumulation and a 2-fold loss in smooth muscle content. Together, these studies demonstrate that supraphysiological levels of androgens cause structural changes in the penile corpora cavernosa and impair fertility. Abstract : Supraphysiological levels of androgens impair penile structure and fertility in mice.